On Question of Existence of Towns in Bashkiria in of Golden Horde Era (13th-14th Centuries) according to Archaeology - I. V. Antonov (Научный диалог)
The question of the Golden Horde towns on the territory of the modern Republic of Bashkortostan is considered. Special attention is paid to those archaeological objects which, according to various researchers, preserve the remains of the Golden Horde towns: Kara-Abyz hillfort in Bladoveshchensk district, Tornaly (Turnaly) hillfort in Salavat district and Ufa II hillfort on the territory of modern Ufa. It is noted that there are no objects of the Golden Horde culture in Kara-Abyz hillfort; only one Golden Horde pottery vessel was found in the Tornaly hillfort; in Ufa II hillfort silver coins of the Golden Horde khans and wire silver earrings, characteristic of the Golden Horde burials, were found, but they make up a scanty part of the numerous and diverse ware material relating mainly to the era of the early middle ages (no later than the 9th century). It is reported that in the 8th-14th centuries on the site of the hillfort there was a small settlement. The novelty of the research is seen in the fact that all considered settlements can not be considered Golden Horde towns. Their further search is unlikely to lead to positive results. It is proved that the territory of Bashkiria was poorly affected by the Golden Horde urban culture, but at the same time it experienced a strong influence of the Golden Horde nomadic culture.